Tubular ACSM3 deficiency impairs medium-chain fatty acid metabolism and aggravates kidney fibrosis - Jinxi Li; Ting Xiang; Fengping Zhang; Li Feng; Yiting Wu; Fan Guo; Lingzhi Li; Ping Fu; Liang Ma (Proceedings of the National Academy of Sciences, 2025)
Kidney fibrosis is driven by multiple factors, among which impaired fatty acid oxidation has emerged as a critical determinant. Acyl-Coenzyme A (CoA) synthetase medium-chain family member 3 (ACSM3), a key enzyme of medium-chain fatty acid (MCFA) metabolism, has been implicated in metabolic syndrome, but its function in fibrotic kidney remains unexplored. Here, we found that tubular epithelial ACSM3 expression was downregulated in kidney fibrotic mice and patients and inversely correlated with disease severity. Systemic and tubular-specific knockout of ACSM3 both exacerbated renal fibrosis, whereas adeno-associated virus (AAV)-mediated ACSM3 overexpression alleviated fibrotic kidneys in mice. Mechanistically, ACSM3 deficiency disrupted MCFA metabolism and resulted in abnormal mitochondrial homeostasis. Notably, we identified that dodecanoic acid (C12:0) could improve kidney fibrosis, which was primarily utilized via ACSM3 in kidneys. Furthermore, C12:0 oxidation impairment caused by tubular ACSM3 deficiency aggravated fibrotic kidney. Together, ACSM3-regulated MCFA metabolism played a pivotal role in kidney fibrosis, highlighting a potent drug target of ACSM3 and a potential supplementary therapy of MCFA against chronic kidney disease.